6(y+2)=42

Simple and best practice solution for 6(y+2)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y+2)=42 equation:


6(y+2)=42

We simplify the equation to the form, which is simple to understand
6(y+2)=42

Reorder the terms in parentheses
+(+6y+12)=42

Remove unnecessary parentheses
+6y+12=+42

We move all terms containing y to the left and all other terms to the right.
+6y=+42-12

We simplify left and right side of the equation.
+6y=+30

We divide both sides of the equation by 6 to get y.
y=5

See similar equations:

| -1-(-2)-7= | | 3(6x-1)=31 | | 8(4d-9)= | | 6x^2-53x=9 | | y/5=-15 | | t^2-8t+9=0 | | 5x+6x-(8x+5)= | | 3tgx=0 | | -3n+5=27 | | 19+8x-25=-7(3-x)+3x | | Senx=-1 | | tgx=0 | | w/2-30=53 | | y+5x-7=0 | | x+4/x-8 | | Y=(18+2x)/8 | | a^2/-3a-6 | | y/3=4 | | 4x^2+12x-7=9 | | n^2/-2n+8 | | 2x^2+25x-2000=0 | | n^2/-2n | | 9-3(x-2)=7+x | | 14/x=7/3 | | (18+2x)/8 | | 5/-8n | | 9x^3+35x^2-4x=0 | | y-3/y-1 | | b^2/7b+7 | | 30x+8x^2=0 | | 3(4+x)=x+16 | | 14/x=7/4 |

Equations solver categories